The C-Terminal Domain of Eukaryotic Initiation Factor 5 Promotes Start Codon Recognition by Its Dynamic Interplay with eIF1 and eIF2β - Rafael E. Luna; Haribabu Arthanari; Hiroyuki Hiraishi; Jagpreet Nanda; Pilar Martin-Marcos; Michelle A. Markus; Barak Akabayov; Alexander G. Milbradt; Lunet E. Luna; Hee-Chan Seo; Sven G. Hyberts; Amr Fahmy; et al. (Cell Reports, 2012)
Recognition of the proper start codon on mRNAs is essential for protein synthesis, which requires scanning and involves eukaryotic initiation factors (eIFs) eIF1, eIF1A, eIF2, and eIF5. The carboxyl terminal domain (CTD) of eIF5 stimulates 43S preinitiation complex (PIC) assembly; however, its precise role in scanning and start codon selection has remained unknown. Using nuclear magnetic resonance (NMR) spectroscopy, we identified the binding sites of eIF1 and eIF2β on eIF5-CTD and found that they partially overlapped. Mutating select eIF5 residues in the common interface specifically disrupts interaction with both factors. Genetic and biochemical evidence indicates that these eIF5-CTD mutations impair start codon recognition and impede eIF1 release from the PIC by abrogating eIF5-CTD binding to eIF2β. This study provides mechanistic insight into the role of eIF5-CTD's dynamic interplay with eIF1 and eIF2β in switching PICs from an open to a closed state at start codons.